2.3. HEAT EQUATION 47
A different derivation of the fundamental solution of the heat equation
appears in §4.3.1.
b. Initial-value problem. We now employ Φ to fashion a solution to the
initial-value (or Cauchy) problem
(8)
ut Δu = 0 in
Rn
× (0, ∞)
u = g on
Rn
× {t = 0}.
Let us note that the function (x, t) Φ(x, t) solves the heat equation
away from the singularity at (0, 0), and thus so does (x, t) Φ(x y, t) for
each fixed y
Rn.
Consequently the convolution
(9)
u(x, t) =
Rn
Φ(x y, t)g(y) dy
=
1
(4πt)n/2
Rn
e−
|x−y|
2
4t
g(y) dy (x
Rn,
t 0)
should also be a solution.
THEOREM 1 (Solution of initial-value problem). Assume g
C(Rn)

L∞(Rn),
and define u by (9). Then
(i) u
C∞(Rn
× (0, ∞)),
(ii) ut(x, t) Δu(x, t) = 0 (x
Rn,
t 0),
and
(iii) lim
(x,t)→(x0,0)
x∈Rn,
t0
u(x, t) =
g(x0)
for each point
x0

Rn.
Proof. 1. Since the function
1
tn/2
e−
|x|
2
4t
is infinitely differentiable, with uni-
formly bounded derivatives of all orders, on
Rn
× [δ, ∞) for each δ 0, we
see that u
C∞(Rn
× (0, ∞)). Furthermore
(10)
ut(x, t) Δu(x, t) =
Rn
[(Φt ΔxΦ)(x y, t)]g(y) dy
= 0 (x
Rn,
t 0),
since Φ itself solves the heat equation.
2. Fix
x0

Rn,
ε 0. Choose δ 0 such that
(11) |g(y)
g(x0)|
ε if |y
x0|
δ, y
Rn.
Previous Page Next Page